Effectiveness of Strategies for Promoting Self‐Care in Heart Failure: A Systematic Review and Network Meta‐Analysis - Yan Zou; Arkers Kwan Ching Wong; Frances Kam Yuet Wong; Jingjing Su; Rose Sin Yi Lin; Ming Ming Liu; Yu Zhang; Nuo Shi (Journal of Advanced Nursing, 2026)
ABSTRACT Aim To compare the effectiveness of different intervention strategies for improving self‐care maintenance, self‐care management and self‐care confidence in adults with heart failure. Design Systematic review and network meta‐analysis. Methods Following PRISMA‐NMA guidelines, randomised controlled trials evaluating heart failure self‐care interventions were included. Self‐care was assessed using the Self‐Care of Heart Failure Index across the eligible studies. Interventions were classified as knowledge/cognition‐oriented, skill/behaviour‐oriented, monitoring/feedback‐reinforcement, motivation/empowerment‐oriented or multicomponent. Risk of bias was assessed with RoB 2. Pairwise meta‐analyses and exploratory network meta‐analyses were performed. Data Sources PubMed, Embase, Scopus, Web of Science, CENTRAL, CINAHL and PsycINFO were searched from inception to March 2025. Results Fifty‐four trials involving 6508 participants were included, of which 32 contributed to the meta‐analysis. In pairwise meta‐analysis, motivation/empowerment‐oriented and skill/behaviour‐oriented interventions improved self‐care maintenance, whereas knowledge/cognition‐oriented, monitoring/feedback‐reinforcement and motivation/empowerment‐oriented interventions improved self‐care management. Multicomponent interventions improved maintenance, management and confidence, but were not clearly superior to more focused strategies. Subgroup analyses suggested greater benefits from personalised provider feedback than from predominantly automated feedback. Exploratory network meta‐analysis showed similar patterns, although rankings should be interpreted cautiously because the network was star‐shaped and lacked direct comparisons between active interventions. Conclusions Heart failure self‐care interventions are not equally effective across domains. Motivation/empowerment‐oriented approaches showed the clearest signal for self‐care maintenance, whereas knowledge‐based and personalised monitoring/feedback strategies appeared more relevant for self‐care management. These findings support a more targeted approach to intervention design. Implications for the Profession Healthcare professionals should tailor strategies to specific self‐care goals, prioritising motivational techniques for maintenance, structured education and monitoring with personalised feedback for management. Patient or Public Contribution No patient or public involvement. Trial Number CRD420250652676